An Approach To Study The Body Back Discomfort Of Economy Class Aircraft Passenger - Tan, Chee Fai; Chen, Wei; Rauterberg, Matthias (2010)
The paper describes the questionnaire study that was designed to unfold the relationship between different body back discomfort levels over time. One hundred and four anonymous self administered questionnaires were completed at Schipol International Airport, the Netherlands from October through November 2008. Long haul economy class aircraft passengers are at risk of uncomfortable for long hour sitting and experience significant uncomfortable at different body back parts such as arm, neck and lower leg.